Influencia de los hábitos alimentarios en la presión arterial en adultos hipertensos del Centro de Salud – Mamey, Cantón Babahoyo, período académico octubre 2024 - mayo 2025. - Hidalgo Delgado, Daniela Lorena (2025)
Eating habits are fundamental and play a crucial role in the prevention, management, and effective control of blood pressure. A detailed analysis of this relationship is crucial, as it offers valuable data to create different intervention strategies. These tactics, in turn, will significantly increase the quality of life of hypertensive patients. In Babahoyo, the Mamey Health Center offers medical care to many adults with hypertension. This group of individuals is especially vulnerable to the adverse effects of an inadequate and unbalanced diet. The aim is to analyze the influence of eating habits on blood pressure in hypertensive adults at the Mamey Health Center, academic period October 2024 - May 2025, by collecting, interpreting, and applying data to propose effective nutritional strategies based on scientific evidence. The research used a mixed qualitative-quantitative method; it was also exploratory and cross-sectional. A survey was applied to 204 adult patients who attended the Mamey Health Center. The study revealed a high consumption of unhealthy foods, including junk food, processed foods, and salt, in hypertensive adults at the Mamey Health Center, which probably aggravates hypertension. This discovery shows the urgent need to change patients' eating habits. In conclusion, it was determined that adopting a healthy diet and reducing risk factors such as excessive consumption of salt, alcohol, and processed foods is crucial to controlling hypertension and improving cardiovascular health in this population.